Statistical Analysis of High-Resolution Light Microscope Images Reveals Effects of Cytoskeleton-Disrupting Drugs on the Membrane Organization of the Nicotinic Acetylcholine Receptor - Wenz, Jorge Javier (2010)
Extensive evidence supports the notion that the cytoskeleton participates in the immobilization and mem- brane clustering of the nicotinic acetylcholine receptor (AChR) at the neuromuscular junction. Stimulated emission depletion fluorescence microscopy has revealed the supra- molecular organization of AChR nanoclusters at the surface of CHO-K1/A5 cells with subdiffraction resolution (Kellner et al., Neuroscience 144:135–143 2007 ). We studied the effect of two cytoskeletal-disrupting drugs (cytochalasin D and jasplakinolide) on the nanoscale distribution of muscle- type AChR expressed in these cells by means of mathe- matical and statistical analysis of images obtained with the same high-resolution microscopy. AChR nanoclusters were found to be randomly distributed in both controls and cells treated with either drug for distances larger than 500 nm. Treatments altered the distribution of AChR nanoclusters according to their brightness/size. Cytochalasin D and jas- plakinolide produced a statistically significant increase in the proportion of medium-size nanoclusters and a diminution of small nanoclusters, indicating higher disrupting activity on the latter. This was further corroborated by the diminution of the brightness/diameter ratio of nanoclusters (a measure of the intracluster density of AChR molecules) and by Ripley’s analysis applied to simulated patterns with intracluster aggregation of AChR molecules. The combined analytical tools bring out subtle changes in the two-dimensional.